Nano antibacterial material for implant surface, and preparation method and application thereof
By preparing Fe/MSAC nanocomposites, the problems of drug resistance, side effects and insufficient antibacterial ability of the existing antibacterial coating on the surface of the implant were solved, effective killing and immune regulation of bacteria were achieved, and implantation was prevented. substance-related infection.
Patent Information
- Application Number
- CN202411694094.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The antibacterial coating on the surface of existing implants has problems such as bacterial resistance, serious side effects and insufficient antibacterial ability, making it difficult to effectively prevent implant-related bacterial infections.
Using Fe/MSAC nanocomplex, BMOF was synthesized by reaction of zinc nitrate, triacetylacetonate and iron and 2-methylimidazole, and pyrolysis was used to obtain FeSAC, and mixed with hyaluronic acid and macrophage membranes to prepare antibacterial and immune regulation. Acting Fe/MSAC nanocomplex.
Fe/MSAC nanocomplexes reduce toxic and side effects on the body when bacteria are free of bacteria, effectively kill pathogenic bacteria when bacteria exist, inhibit the formation of biofilms, and regulate the body's immune response, achieving the effect of preventing infection.
Smart Images

Figure HDA0005151705060000011 
Figure HDA0005151705060000012 
Figure HDA0005151705060000013
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a nanoenzyme antibacterial coating for an implant surface, a preparation method thereof and an application thereof. Background Art
[0002] Orthopedic biological implants are materials that can repair bone defects or bone function. The presence of bacterial colonization or bacterial biofilm on orthopedic implants will cause delayed healing or bone loss risks to patients, leading to implant treatment failure. In severe cases, a secondary surgery is required to remove the implant or even amputate. It is very important to prevent and reduce bacterial infection problems caused by implants.
[0003] So far, patients still need to take antibiotics after surgery to deal with potential infection risks. Some implant antibacterial coatings based on antibiotics and polymer materials have been developed. Although these methods can kill pathogens or inhibit bacterial adhesion, they still face problems such as bacterial resistance, serious side effects and weak antibacterial ability, and most of the antibacterial coatings are non-selective antibacterial coatings. Therefore, it is very important to develop selective antibacterial nano-antibacterial coating materials that will not cause bacterial resistance and have low side effects and good antibacterial properties. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a nano antibacterial material for the surface of an implant, a preparation method thereof and an application thereof.
[0005] The present invention provides a method for preparing a Fe / MSAC nanocomposite, which comprises the following steps:
[0006] Step 1, zinc nitrate, triacetylacetonate iron and 2-methylimidazole react to obtain BMOF;
[0007] Step 2, the BMOF is pyrolyzed to obtain FeSAC;
[0008] Step 3: Mix the FeSAC, hyaluronic acid and macrophage membrane to obtain Fe / MSAC.
[0009] Furthermore,
[0010] The zinc nitrate, triacetylacetonate iron (Fe(acac) 3) and 2-methylimidazole concentration ratio is (2-3): (0.4-0.6): (9-12); further (2.5-2.8): (0.5-0.6): (10-11); further (2.5-2.7): (0.5-0.55): (10-10.5); In a specific embodiment of the present invention, 30 mL of a methanol solution containing 4 mmol zinc nitrate and 0.8 mmol triacetylacetonate iron is mixed with 15 mL of a methanol solution containing 16 mmol 2-methylimidazole;
[0011] In the present invention, some of the three substances of zinc nitrate, triacetylacetonate iron and 2-methylimidazole are dissolved separately, then mixed, and then stirred after mixing to ensure that the above substances are fully mixed, thereby being more conducive to the reaction between the above substances; the separate dissolution, stirring, etc. are all conventional steps taken to achieve sufficient mixing. Those skilled in the art can achieve the reaction of the above three substances to obtain BMOF by adjusting the type of solvent for dissolving the substances, stirring speed, temperature and other parameters, which are all within the protection scope of the present invention.
[0012] The reaction conditions are: 100-140°C, 2-10h; specifically 120°C, 4h;
[0013] The reaction further includes the steps of centrifugation, rinsing and drying; the drying condition is 50-90°C, and further drying at 70°C for 8-12h. Appropriately shortening or extending the drying time is within the scope of protection of the present invention.
[0014] The pyrolysis conditions are: nitrogen protection, initial temperature of 20-30°C, specifically 25°C, heating rate of 5°C / min, heating to 900°C for 3h.
[0015] The concentration ratio of FeSAC to hyaluronic acid is (5-15):(0.5-1.5); further (9-11):(0.8-1.2); in a specific embodiment of the present invention, it is 10:1.
[0016] In the present invention, FeSAC (1 mg / mL) and hyaluronic acid (HA, 0.1 mg / mL) are first mixed, and the specific mixing is stirring at room temperature in the dark for 4 hours; then the suspension obtained by mixing FeSAC (1 mg / mL) and hyaluronic acid (HA, 0.1 mg / mL) is mixed with the macrophage membrane;
[0017] In the preparation method of the present invention, the mixing of the FeSAC, hyaluronic acid and macrophage membrane further includes the steps of centrifugation and washing; the centrifugation condition is 12000rpm, 10min;
[0018] The present invention obtains an Fe / MSAC nanocomposite, which has antibacterial and immunomodulatory effects. The Fe / MSAC nanocomposite is applied to the surface of a graft for antibacterial treatment of the graft surface. Test results show that the Fe / MSAC nanocomposite has high safety and reduces toxic side effects on the body when there are no bacteria. In addition, the Fe / MSAC nanocomposite can effectively kill pathogenic bacteria that can degrade hyaluronic acid when bacteria are present, inhibit the formation of biofilms, and regulate the body's immune response to achieve the effect of preventing infection. At the same time, the present invention adjusts the material ratio, parameter settings and steps for obtaining the Fe / MSAC nanocomposite, and obtains the Fe / MSAC nanocomposite as recorded in the present invention (such as the ratio of zinc nitrate, triacetylacetonate iron and 2-methylimidazole, specifically, the zinc nitrate, triacetylacetonate iron (Fe(acac) 3 ) and 2-methylimidazole concentration ratios are (2-3): (0.4-0.6): (9-11), (2-3): (0.2-0.3): (9-11), and (2-3): (1.2-1.8): (9-11), respectively. These three ranges are optimized; finally, after comparison, the performance of the Fe / MSAC nanocomposite prepared at a concentration ratio of (2.5-2.7): (0.5-0.55): (10-10.5) is optimal; such as the pyrolysis reaction temperature, 700°C, 800°C, and 900°C are selected. Finally, the performance of the Fe / MSAC nanocomposite prepared at a temperature of 900°C is optimal), and its performance is better than that of the composites with other material ratios, parameters and step settings.
[0019] Moreover, compared with the material of CN 118236508 A, the Fe / MSAC nanocomposite of the present invention is not able to inhibit the formation of bacterial biofilm and has no immunomodulatory effect.
[0020] The invention provides a Fe / MSAC nanocomposite prepared by the preparation method.
[0021] The present invention provides a Fe / MSAC nanocomposite preparation, which includes an auxiliary material and at least one of the following I) to II):
[0022] 1) Fe / MSAC nanocomposite prepared by the preparation method of the present invention;
[0023] II), the Fe / MSAC nanocomposite described in the present invention.
[0024] The auxiliary materials include: buffer, antioxidant, buffer, pH regulator, thickener, antibiotic and / or preservative, etc.
[0025] The present invention provides an antibacterial composition, which comprises an antibacterial substance and at least one of the following I) to III):
[0026] I), the present invention provides a Fe / MSAC nanocomposite prepared by the preparation method;
[0027] II), the present invention provides the Fe / MSAC nanocomposite;
[0028] III), the present invention provides the Fe / MSAC nanocomposite preparation.
[0029] Furthermore, the antibacterial substances include antibacterial peptides, antibiotics, sulfonamides, imidazoles, nitroimidazoles, quinolones and other chemically synthesized drugs, which are not limited in the present invention.
[0030] The present invention provides the use of at least one of the following A) to D) in inhibiting or killing pathogens and / or immunomodulating:
[0031] A), the present invention provides a Fe / MSAC nanocomposite prepared by the preparation method;
[0032] B), the present invention provides the Fe / MSAC nanocomposite;
[0033] C), the present invention provides the Fe / MSAC nanocomposite preparation;
[0034] D) The present invention provides the antibacterial composition.
[0035] Furthermore, the pathogen secretes hyaluronidase.
[0036] The present invention provides a method for inhibiting or killing pathogens and / or immunomodulation, which utilizes at least one of the following a) to d):
[0037] a), the present invention provides a Fe / MSAC nanocomposite prepared by the preparation method;
[0038] b), the present invention provides the Fe / MSAC nanocomposite;
[0039] c) The present invention provides the Fe / MSAC nanocomposite preparation;
[0040] d) The present invention provides the antibacterial composition.
[0041] The invention provides an Fe / MSAC nanocomposite for an implant surface. The Fe / MSAC nanocomposite is made of FeSAC containing a single iron atom catalytic site, which encapsulates hyaluronic acid and a macrophage membrane. The Fe / MSAC nanocomposite is used on the implant surface, is safe and stable, reduces toxic side effects on an organism when there are no bacteria, and can effectively kill Staphylococcus aureus when bacteria are present, inhibit the formation of biofilms, and regulate the body's immune response, thereby achieving an effect of preventing infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Shows the SEM image of BMOF, the scale bar is 400 nm;
[0043] Figure 2 TEM and HAADF-STEM images of FeSAC are shown, where the circles represent single Fe atoms, the scale bar in Figure A is 200 nm, and the scale bar in Figure B is 5 nm;
[0044] Figure 3 shows the X-ray energy spectrum (EDS) diagram of FeSAC;
[0045] Figure 4 Figure 1 shows the synchrotron radiation analysis results of FeSAC, where A is the X-ray absorption near-edge structure (XANES) curve; B is the Fourier transform (FT) κ of FeSAC 3 Weighted EXAFS spectrum; C is the EXAFS fitting curve corresponding to FeSAC in R space; D is the EXAFS fitting curve corresponding to FeSAC in k space; E is FeSAC, Fe and Fe 2 O 3 Wavelet transform image of
[0046] Figure 5 The hydrated particle size and Zeta potential of FeSAC and Fe / MSAC are shown;
[0047] Figure 6 Shown is the enzyme kinetics test diagram of FeSAC;
[0048] Figure 7 Figure 2 shows the antibacterial test results of Fe / MSAC;
[0049] Figure 8 The biofilm inhibition experiment of Fe / MSAC is shown;
[0050] Fig. 9 The graphs showing the bacterial survival rates on titanium rods of different groups;
[0051] Fig.10 It shows the immunomodulatory effect of Fe / MSAC;
[0052] Fig.11It showed that Fe / MSAC had no obvious cytotoxicity to macrophages;
[0053] Fig.12 It showed that Fe / MSAC had no significant effect on the main organs of mice;
[0054] Fig.13 It showed that there was no significant effect on the blood routine, liver function and kidney function of Fe / MSAC mice;
[0055] Fig.14 It showed that Fe / MSAC had no significant effect on the weight change of mice;
[0056] Fig.15 Figure 3 shows the biotherapeutic effect of Fe / MSAC nanozyme bionic coating on the implant surface, where A is a photo of abscess at the implantation site in mice; B is a photo of the colonies and culture medium in each group; C is the SEM image of titanium rods in different groups; and D is the H&E image of skin tissue in each group. DETAILED DESCRIPTION
[0057] The present invention provides nanoenzyme antibacterial materials for implant surfaces, preparation methods and applications thereof. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be noted in particular that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0058] The test materials used in the present invention are all common commercial products and can be purchased on the market. The present invention is further described below in conjunction with the embodiments:
[0059] Example 1 Synthesis of Fe / MSAC
[0060] 1. Synthesis of BMOF
[0061] 30 mL Zn(NO 3 ) 2 6H 2 O(Zn nitrate, 4mmol) and Fe(acac) 3 The homogeneous methanol solution of (triacetylacetonate iron, 0.8 mmol) and 15 mL of 2-methylimidazole (16 mmol) methanol solution were gently stirred for 1 hour, and then the mixture was transferred to a stainless steel hydrothermal synthesis reactor, sealed, and heated to 120°C for 4 hours. After cooling, the BMOF was collected, centrifuged, rinsed, and finally dried in a vacuum oven at 70°C overnight. The SEM image of the BMOF is shown in the figure. Figure 1 shown.
[0062] 2. Synthesis of FeSAC
[0063] The obtained BMOF was ground into powder, loaded into a porcelain boat, and pyrolyzed at 900°C for 3 hours in a tube furnace under nitrogen protection, with a heating rate of 5°C / min. After cooling, the obtained FeSAC was collected. The TEM and HAADF-STEM images of FeSAC are shown in Figure 2. Figure 2 shown.
[0064] 3. X-ray energy spectrum (EDS) diagram verifies the elemental composition of the material.
[0065] The present invention further uses X-ray spectroscopy to verify the elemental composition of the material. Figure 3 As shown, the material contains iron.
[0066] 4. Verify the coordination environment of the iron element in the material.
[0067] The present invention further uses synchrotron radiation element analysis experiments to verify the coordination environment of the iron element in the material. Figure 4 As shown, a series of experiments confirmed that Fe-N 4 coordination structure.
[0068] 5. Synthesis of Fe / MSAC.
[0069] FeSAC (final concentration 1 mg / mL) was mixed with hyaluronic acid (HA, final concentration 0.1 mg / mL), stirred in the dark at room temperature for 4 hours to obtain a suspension. Finally, the macrophage membrane was coated by continuous extrusion. The suspension with a concentration of 200 μg / mL was mixed with the macrophage membrane in PBS. The mixture was transferred into a syringe, extruded through a 450 nm membrane filter multiple times, centrifuged at 12000 rpm for 10 minutes, washed with water to remove excess macrophage membrane (extracted from 10e7 cells), and Fe / MSAC was obtained and stored at -80°C. The hydrated particle size and Zeta potential of Fe / MSAC are shown in Figure 5 shown.
[0070] 6. Enzyme activity test of FeSAC.
[0071] The enzyme activity of FeSAC was tested by TMB (3,3',5,5'-tetramethylbenzidine) color reaction. Kinetic analysis was performed on a Jasco-V550 UV-visible spectrophotometer using the time course mode to monitor the change in absorbance at 652 nm. The Michaelis constant was calculated using the Lineweaver Burk formula: 1 / ν = (K m / V max ) / C+1 / V max , where ν is the initial velocity, V max is the maximum reaction rate, C is the substrate concentration. 2 O2 The time course and enzyme kinetic curves of TMB and substrate are shown in the figure. Figure 6 As shown, FeSAC has a lower Km and a higher Vmax value, which not only makes it easy to adsorb substrates but also catalyzes oxidation at a fast rate, indicating that FeSAC has significant peroxidase-like ability.
[0072] Example 2 Determination of the antibacterial properties of Fe / MSAC.
[0073] 1. Selective antibacterial ability of Fe / MSAC
[0074] The present invention uses Staphylococcus aureus and Escherichia coli to investigate the selective antibacterial ability of Fe / MSAC. Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were used, and the bacterial concentration was adjusted to 10 4 CFU / mL, and the concentration was 50 μg mL -1 Fe / MSAC, 100×10 -6 M's H 2 O 2 , and a mixture of hyaluronic acid and macrophage membranes (MHA, approximately 10 μg mL -1 ), in which the ratio of hyaluronic acid to macrophage membrane was approximately 1:1; the control group was treated with sterile PBS;
[0075] Since Staphylococcus aureus can secrete hyaluronidase to degrade the hyaluronic acid of Fe / MSAC, Fe / MSAC is then 2 O 2 In the presence of , active oxygen is produced, killing bacteria. Figure 7 As shown, it is explained that the invention has a significant selective removal effect on Staphylococcus aureus, but has no killing effect on Escherichia coli.
[0076] 2. Biofilm inhibition experiment of Fe / MSAC.
[0077] The present invention uses Staphylococcus aureus to investigate the ability of Fe / MSAC to inhibit the formation of membrane. The control group was treated with sterile PBS; MHA was treated with a mixture of hyaluronic acid and macrophage membrane (MHA, about 10 μg mL -1 ), where the ratio of hyaluronic acid to macrophage membrane is approximately 1:1; the FeSAC concentration is 50 μg mL -1 ; Fe / MSAC concentration was 50 μg mL -1 The above substances are respectively 8 After incubation with CFU / mL of Staphylococcus aureus, the cells were cultured in TSB medium. Figure 8As shown, the Fe / MSAC treatment greatly inhibited the formation of biofilm, indicating that the invention has a significant inhibitory effect on biofilm.
[0078] 3. Fe / MSAC is used in anti-infection experiments on implant surfaces.
[0079] The Fe / MSAC used for the implant surface used in the present invention was pretreated with Staphylococcus aureus and then implanted subcutaneously in mice. The implants were taken out after 5 days and cultured in bacterial LB culture medium. The bacterial survival rates on the titanium rods of different groups were counted by colony counting method. The results are as follows: Fig. 9 (Ti is titanium rod implanted directly; Ti / HAM is titanium rod implanted with hyaluronic acid and cell membrane; Ti-FeSAC is titanium rod implanted with FeSAC, and the amount of FeSAC used is about 0.2 g / m 2 ; Ti-Fe / MSAC coated Fe / MSAC titanium rod implantation, the amount of Fe / MSAC used is about 0.2g / m 2 ). The results show that the nanozyme antibacterial coating used on the implant surface in the present invention has good anti-infection ability.
[0080] 4. Immunomodulatory effect of Fe / MSAC
[0081] Fe / MSAC can regulate the body's immune function and simulate the body's innate immune response while killing bacteria, and has greater application potential. The present invention uses MOF as a matrix to synthesize single-atom nanozymes, which can simulate the natural immune system to resist bacteria and resist membranes. On the one hand, single-atom nanozymes have peroxidase-like activity and can produce reactive oxygen species, simulating neutrophils to directly kill bacteria and inhibit bacterial membranes. On the other hand, they can recruit and polarize macrophages to kill bacteria and restore the immunosuppressive microenvironment. Fig.10 , where 1 is PBS treatment; 2 is 100×10 -6 M concentration of H 2 O 2 Treatment; 3 is 50 μg mL -1 concentration Fe / MSAC treatment; 4 is Fe / MSAC+H 2 O 2 treatment, where the concentration of Fe / MSAC was 50 μg mL -1 , H 2 O 2 The concentration is 100×10 -6 M; the above substances were incubated with macrophages, and the expression of macrophage cytokines was detected; the results showed that the nanozyme coating induced macrophages to polarize toward the M1 type, and the secretion of pro-inflammatory cytokines increased.
[0082] 5. Security
[0083] Cytotoxicity tests and animal experiments showed that Fe / MSAC had no significant cytotoxicity to macrophages ( Fig.11 ); no significant effect on the main organs of mice ( Fig.12 , the control group was healthy mice without treatment), and there was no significant effect on the blood routine, liver function and kidney function of mice ( Fig.13 , where WBC is white blood cell, RBC is red blood cell, PLT is platelet, MCH is mean corpuscular hemoglobin content, MCV is mean corpuscular volume, HCT is hematocrit, BUN is blood urea nitrogen, CREA is serum creatinine (Crea), ALT is alanine aminotransferase, ALB is serum albumin, GLB is globulin, TB is total bilirubin), and the weight changes were no different from those of normal mice ( Fig.14 , compared with Fig.12 ). The coated macrophage membrane and hyaluronic acid can target bacteria and be degraded by hyaluronidase secreted by bacteria, enhancing the specificity of the system without harming normal cells.
[0084] On the one hand, the present invention does not involve antibiotics, does not have the problem of antibiotic resistance, and uses enzyme-like activity to generate oxygen free radicals to kill bacteria, so the risk of drug resistance is lower. On the other hand, the hyaluronic acid coating makes the material work only when bacteria are present, and the hyaluronidase secreted by the bacteria degrades the nanoparticle shell, so the risk of bacterial resistance is low.
[0085] 6. Biotherapeutic effect of Fe / MSAC nanozyme biomimetic coating on implant surface
[0086] An implant-induced infection model was established to study the biotherapeutic effect of the nanozyme biomimetic coating on the implant surface. Untreated Ti rods, Ti-HAM rods, Ti-FeSA rods, and Ti-FeSA / HAM rods were soaked in a suspension of Staphylococcus aureus overnight and then implanted subcutaneously in the left hind limb of mice to observe wound healing and abscess formation at the subcutaneous implantation site. After 7 days, the epidermis of the surgical site of mice in the nanozyme biomimetic coating group regenerated and healed well, while the other groups all developed varying degrees of swelling and pustules ( Fig.15 A in the figure). Titanium rods from each group were collected after the experiment and cultured with LB medium. The culture medium of the nanozyme coating group was clear and there were almost no colonies on the plate, indicating that the coating effectively killed bacteria and prevented the growth of biofilm on its surface ( Fig.15 B in the figure). Scanning electron microscopy showed that the surface of the titanium rod in the nanozyme coating group was relatively smooth and almost free of bacteria ( Fig.15 C). Hematoxylin and eosin (H&E) staining of surrounding skin tissue showed that the nanozyme coating group had a milder inflammatory response, fewer inflammatory cells, and better epidermal healing ( Fig.15 D).
[0087] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing Fe / MSAC nanocomposites, characterized in that: The steps include: Step 1, zinc nitrate, triacetylacetonate iron and 2-methylimidazole react to obtain BMOF; Step 2, the BMOF is pyrolyzed to obtain FeSAC; Step 3: Mix the FeSAC, hyaluronic acid and macrophage membrane to obtain Fe / MSAC.
2. The preparation method according to claim 1, characterized in that: The concentration ratio of the zinc nitrate, triacetylacetonate iron (Fe(acac)3) and 2-methylimidazole is (2-3): (0.4-0.6): (9-11).
3. The preparation method according to claim 1, characterized in that: The reaction conditions are: 100-140° C., 2-10 h.
4. The preparation method according to claim 1, characterized in that: The pyrolysis conditions are: nitrogen protection, initial temperature of 20°C to 25°C, heating rate of 5°C / min, heating to 900°C for 3h.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the FeSAC to the hyaluronic acid is (5-15):(0.5-1.5).
6. The Fe / MSAC nanocomposite prepared by the preparation method according to any one of claims 1 to 5.
7. Fe / MSAC nanocomposite preparation, characterized in that It includes auxiliary materials and at least one of the following I) to II): I), Fe / MSAC nanocomposite prepared by the preparation method according to any one of claims 1 to 5; II), the Fe / MSAC nanocomposite according to claim 6.
8. An antibacterial composition, characterized in that It includes antibacterial substances and at least one of the following I) to III): I), Fe / MSAC nanocomposite prepared by the preparation method according to any one of claims 1 to 5; II), the Fe / MSAC nanocomposite according to claim 6; III), the Fe / MSAC nanocomposite preparation according to claim 7.
9. Use of at least one of the following A) to D) in inhibiting or killing pathogens and / or immunomodulation: A), Fe / MSAC nanocomposite prepared by the preparation method according to any one of claims 1 to 5; B), the Fe / MSAC nanocomposite according to claim 6; C) the Fe / MSAC nanocomposite preparation according to claim 7; D) The antibacterial composition according to claim 8.
10. The use according to claim 9, characterized in that: The pathogen secretes hyaluronidase.
11. A method for inhibiting or killing pathogens and / or immunomodulating, characterized in that: To utilize at least one of the following a) to d): a), Fe / MSAC nanocomposite prepared by the preparation method according to any one of claims 1 to 5; b) the Fe / MSAC nanocomposite according to claim 6; c) the Fe / MSAC nanocomposite preparation according to claim 7; d) The antibacterial composition according to claim 8.